Interval Oscillation Theorems for the Weighted p-Sub-Laplacian Equation in the Heisenberg Group - Duan Wu; Pengcheng Niu (Advances in Mathematical Physics)
In this paper, we derive a Riccati-type inequality in the Heisenberg group Hn. Based on it, some oscillation criteria are established for the weighted p-sub-Laplacian equations in Hn. Our results generalize the oscillation theorems for p-sub-Laplacian equations in Rn to ones in Hn.